2015
DOI: 10.1136/bmjopen-2014-007516
|View full text |Cite
|
Sign up to set email alerts
|

Direct targeting of risk factors significantly increases the detection of liver cirrhosis in primary care: a cross-sectional diagnostic study utilising transient elastography

Abstract: ObjectivesTo assess the feasibility of a novel diagnostic algorithm targeting patients with risk factors for chronic liver disease in a community setting.DesignProspective cross-sectional study.SettingTwo primary care practices (adult patient population 10 479) in Nottingham, UK.ParticipantsAdult patients (aged 18 years or over) fulfilling one or more selected risk factors for developing chronic liver disease: (1) hazardous alcohol use, (2) type 2 diabetes or (3) persistently elevated alanine aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 45 publications
3
110
0
2
Order By: Relevance
“…In the three studies (19,28,29) which utilised TE the reported disease prevalence was similar despite two different thresholds being chosen and the reported outcome measures being different.…”
Section: Aldmentioning
confidence: 93%
See 1 more Smart Citation
“…In the three studies (19,28,29) which utilised TE the reported disease prevalence was similar despite two different thresholds being chosen and the reported outcome measures being different.…”
Section: Aldmentioning
confidence: 93%
“…Harman et al (29) was the only study which reported the percentage of patients with a normal ALT level who were diagnosed with cirrhosis. In this study 90.9% of patients with asymptomatic compensated cirrhosis would not have been identified via traditional community based algorithms.…”
Section: Alt Levels and Predictors Of Significant Liver Diseasementioning
confidence: 99%
“…Most interestingly, 71/98 patients (72.4%) of these patients had normal liver enzymes and would have been otherwise missed by conventional algorithm models. This techniques also managed to identify 140% more patients with definite cirrhosis ( n = 11)[123]. …”
Section: Imaging-based Modalities As Alternatives To Biopsymentioning
confidence: 99%
“…TE was offered to primary care patients with an AST:ALT ratio ≥ 0.8 [224]. However, This study did not include biopsy confirmation in patients with elevated TE.…”
Section: Screening the General Population Or High-risk Groups In Primmentioning
confidence: 99%